2001
DOI: 10.1086/324267
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle Myosin Heavy Chain IIA Mutations Define a Spectrum of Autosomal Dominant Macrothrombocytopenias: May-Hegglin Anomaly and Fechtner, Sebastian, Epstein, and Alport-Like Syndromes

Abstract: May-Hegglin anomaly (MHA) and Fechtner (FTNS) and Sebastian (SBS) syndromes are autosomal dominant platelet disorders that share macrothrombocytopenia and characteristic leukocyte inclusions. FTNS has the additional clinical features of nephritis, deafness, and cataracts. Previously, mutations in the nonmuscle myosin heavy chain 9 gene (MYH9), which encodes nonmuscle myosin heavy chain IIA (MYHIIA), were identified in all three disorders. The spectrum of mutations and the genotype-phenotype and structure-funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
234
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(238 citation statements)
references
References 43 publications
(53 reference statements)
1
234
1
2
Order By: Relevance
“…We did this by mutating Arg709 to Cys, thereby duplicating a mutation that had previously been shown to occur in humans for NMHC II-A (Heath et al, 2001). Interestingly, the homologous residue has also been shown to be mutated in NMHC II-C, although, in this case, to a serine residue (Donaudy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We did this by mutating Arg709 to Cys, thereby duplicating a mutation that had previously been shown to occur in humans for NMHC II-A (Heath et al, 2001). Interestingly, the homologous residue has also been shown to be mutated in NMHC II-C, although, in this case, to a serine residue (Donaudy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A mutation of MYH9 alone does not seem to cause associated Alport manifestations, and unknown genetic and/or epigenetic factors might influence the phenotypic consequences of MYH9 mutations. [7][8][9][10] Although the molecular mechanisms of hematologic abnormalities are under investigation, those of the kidney, cochlea, and lens are completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A mutation of MYH9 alone does not seem to cause associated Alport manifestations, and unknown genetic and/or epigenetic factors might influence the phenotypic consequences of MYH9 mutations. [7][8][9][10] Although the molecular mechanisms of hematologic abnormalities are under investigation, those of the kidney, cochlea, and lens are completely unknown.We previously showed that NMMHC-IIA polypeptide accumulates in neutrophil cytoplasm and forms inclusion bodies in patients with MYH9 disorders. The nature of the cytoplasmic accumulation can be classified according to the number, size, and shape of accumulated NMMHC-IIA granules, into types I, II, and III.…”
mentioning
confidence: 99%
“…Although they were previously considered to be separate clinical entities, it is now established that all four disorders are caused by mutations in the MYH9 gene. Therefore, the name ''MYH9 disorder'' or ''MYH9-related disease'' has been proposed [15,[19][20][21]. To date, about 200 families with MYH9 disorders have been studied, in which 30 distinct mutations in the MYH9 gene have been identified [19][20][21][22].…”
Section: Related Disorders and Unsolved Issuesmentioning
confidence: 99%
“…Therefore, the name ''MYH9 disorder'' or ''MYH9-related disease'' has been proposed [15,[19][20][21]. To date, about 200 families with MYH9 disorders have been studied, in which 30 distinct mutations in the MYH9 gene have been identified [19][20][21][22]. The majority of patients are heterozygous for missense mutations and some patients are heterozygous for nonsense or frameshift mutation in the last exon.…”
Section: Related Disorders and Unsolved Issuesmentioning
confidence: 99%